Induction of pathogenesis-related gene 1 (PR-1) by acibenzolar-s-methyl application in pineapple and its effect on reniform nematodes (Rotylenchulus reniformis) - Chinnasri, Buncha; Borsics, Tamas; Christopher, David A.; Sipes, Brent S. (Agriculture and Natural Resources, 2016)
The induction of systemic acquired resistance (SAR) in pineapples (Ananas comosus) was studied as shown by the up-regulation of the PR-1 gene (the SAR marker) and examination of the SAR effect on the reniform nematode, Rotylenchulus reniformis. Real-time polymerase chain reaction assay was performed using degenerate primers designed from the PR-1 genes of several monocotyledonous (monocots) and dicotyledonous (dicots) plants. A 266 bp cDNA band was evident only in plants treated with the SAR inducer, acibenzolar-s-methyl. This 266 bp cDNA was sequenced and found to be highly homologous to a number of PR-1 genes from monocots. In addition, the amino acid sequence deduced from the 266 bp cDNA showed a high identity to PR-1 proteins from both monocots and dicots. Therefore, it was highly likely that this cloned fragment was part of the A. comosus PR-1 gene, indicating that A. comosus has an SAR pathway. The time course of PR-1 expression was studied. The results showed that PR-1 induction was initiated as early as 1 d after acibenzolar application and continued through 3 wk thereafter. The effect of SAR on the nematodes, R. reniformis, in pineapples was also elucidated. The results showed that the reproduction of nematodes on the pineapples treated with 100 mg/L or 200 mg/L was 55% lower than that on pineapples treated with 0 mg/L or 50 mg/L. Nematode reproduction on pineapples treated with the same concentration but inoculated at different times was not significantly different (p > 0.05).